Carbon‐based materials for all‐solid‐state zinc–air batteries. Issue 1 (10th November 2020) - Yang, Dan; Chen, Dong; Jiang, Yu; Ang, Edison Huixiang; Feng, Yuezhan; Rui, Xianhong; Yu, Yan
Abstract: Solid‐state Zn–air batteries (ZABs) hold great potential for application in wearable and flexible electronics. However, further commercialization of current ZABs is still limited by the poor stability and low energy efficiency. It is, thus, crucial to develop efficient catalysts as well as optimize the solid electrolyte system to unveil potential of the ZAB technology. Due to the low cost and versatility in tailoring the structures and properties, carbon materials have been extensively used as the conductive substrates, catalytic air electrodes, and important components in the electrolytes for the solid‐state ZABs. Within this context, we discuss the challenges facing current solid‐state ZABs and summarize the strategies developed to modify properties of carbon‐based electrodes and electrolytes. We highlight the metal−organic framework/covalent organic framework‐based electrodes, heteroatom‐doped carbon, and the composites formed of carbon with metal oxides/sulfides/phosphides. We also briefly discuss the progress of graphene oxide‐based solid electrolyte. Abstract : Commercialization of high‐performance solid‐state Zn–air batteries (ZABs) has remained an intriguing, yet challenging, task to date. With the versatility in tuning the structures and properties, low‐cost carbonaceous materials hold great promise to fill this gap. To summarize the encouraging progress achieved over the past decades, here we reviewed the structures, properties, and modification strategies of various types of carbon‐based electrodes/electrolytes for solid‐state ZABs.